2010
DOI: 10.1111/j.1532-5415.2010.02718.x
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Mobility in Older Adults

Abstract: OBJECTIVES: To determine the influence of homocysteine on mobility decline in older adults. DESIGN: Prospective cohort. SETTING: Einstein Aging Study, community‐based aging study. PARTICIPANTS: Five hundred seventy‐four older adults without dementia (mean age 80.2 ± 5.4, 61% women). MEASUREMENTS: Mobility decline defined using gait velocity measurements at baseline and annual follow‐up visits. Linear mixed effects models were used to adjust for age, sex, education, and other potential confounders. RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
3
18
1
Order By: Relevance
“…For vitamin B12 in women, and for homocysteine and vitamin B12 in men, the observed associations were less consistent. This study partly confirms the results of five earlier studies that observed an association between homocysteine and physical performance in the general older population (Kado et al, 2002;Soumare et al, 2006;Gerdhem et al, 2007;Kuo et al, 2007;Rolita et al, 2010). In addition, this study confirms the presence of a longitudinal association between homocysteine and physical performance of two earlier studies (Kado et al, 2002;Rolita et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…For vitamin B12 in women, and for homocysteine and vitamin B12 in men, the observed associations were less consistent. This study partly confirms the results of five earlier studies that observed an association between homocysteine and physical performance in the general older population (Kado et al, 2002;Soumare et al, 2006;Gerdhem et al, 2007;Kuo et al, 2007;Rolita et al, 2010). In addition, this study confirms the presence of a longitudinal association between homocysteine and physical performance of two earlier studies (Kado et al, 2002;Rolita et al, 2010).…”
Section: Discussionsupporting
confidence: 82%
“…This study partly confirms the results of five earlier studies that observed an association between homocysteine and physical performance in the general older population (Kado et al, 2002;Soumare et al, 2006;Gerdhem et al, 2007;Kuo et al, 2007;Rolita et al, 2010). In addition, this study confirms the presence of a longitudinal association between homocysteine and physical performance of two earlier studies (Kado et al, 2002;Rolita et al, 2010). In the first three studies, the association between homocysteine and physical performance was observed in a combined sample of men and women (Kado et al, 2002;Soumare et al, 2006;Kuo et al, 2007).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations